Electron Resonant Interaction With Whistler Waves Around Foreshock Transients and the Bow Shock Behind the Terminator. Issue 2 (14th February 2022) - Artemyev, A. V.; Shi, X.; Liu, T. Z.; Zhang, X.‐J.; Vasko, I.; Angelopoulos, V.
Abstract: Investigation of electron energization at (and around) the Earth's bow shock is critical to our understanding of space weather and astrophysical phenomena. The traditional adiabatic mechanisms for such energization compete with transient wave‐particle interactions there. One of the most intense wave modes resonating with electrons is the high‐frequency whistler mode, which is widely observed at (and around) the Earth's bow shock. Here, we examine these interactions in the context of the strong magnetic field gradients often found near the bow shock and at foreshock transients. Using THEMIS and ARTEMIS wave measurements, we quantify the nonlinear effects of resonant interactions between ≥100 eV electrons and intense coherent whistler waves. Such nonlinear interactions include the electron phase trapping by waves. As a result, the trapped electrons gain an energy up to several hundreds of eV. We estimate the main characteristics of the proposed acceleration mechanism and discuss its applicability to realistic plasma and magnetic field distributions. Key Points: High‐frequency whistler waves at the bow shock behind the terminator and foreshock transients are investigated Resonant electron interaction with whistler waves is analyzed quantitatively Nonlinear resonant phase trapping by whistler waves is shown to cause effective electron acceleration